Cardiotoxicity by Anthracycline Regimen Chemotherapy Prolonged T Peak to T End Interval - Iqbal, Mohammad (Cardiol Res, 2020)
BACKGROUND: Myocardial necrosis may occur due to anthracycline (doxorubicin/adriamycin) chemotherapy usage. Furthermore, myocardial necrosis can affect the heterogeneity of heart conduction system and lead to repolarization abnormalities. The aim of this study was to investigate the effect of cardiotoxicity caused by anthracycline to repolarization abnormalities measured by T peak to T end (TpTe) interval. METHODS: This was a single center prospective cohort study with linear regression from October 2018 to May 2019. The subjects of the study were breast cancer patients after completing administration of chemotherapy with fluorouracil, adriamycin and cyclophosphamide (FAC) regimen (containing anthracycline) for 6 months. Myocardial necrosis was assessed by high sensitive (hs)-troponin I, and the heterogeneity of repolarization was measured by TpTe interval. RESULTS: This study involved 25 breast cancer patients after chemotherapy in the 6-month FAC regimen. The mean age is 46 ± 7 years, and the cumulative dose of anthracycline is 591 ± 52 mg/m(2). The mean level of hs-troponin I is 90.5 ± 44.7 ng/L and the TpTe interval is 108.2 ± 10 ms. The results of linear regression analysis showed a positive correlation between hs-troponin I and TpTe interval (r: 0.421, P: 0.036) after controlling for one confounding variable (cumulative dose of anthracycline). CONCLUSIONS: Cardiotoxicity caused by accumulative dose of anthracycline may lead to myocardial necrosis which was shown by elevated hs-troponin I levels. This process may lead to heterogeneity conduction system that affect the repolarization phase of cardiac cycle which was shown by increased TpTe interval.